Expression of Matrix Metalloproteinase-7 Predicts Poor Prognosis in Gastric Cancer. (22nd April 2022) - Wattanawongdon, Wareeporn; Bartpho, Theeraya Simawaranon; Tongtawee, Taweesak
Abstract : To date, no potential markers have been established for predicting prognosis in gastric cancer. Matrix metalloproteinase-7 (MMP-7) has been suggested as a prognostic marker in several cancers. In this study, we aimed to determine the expression of the MMP-7 protein and its polymorphisms in gastric cancer tissues. The association between MMP-7 expression level and clinicopathological characteristics was also evaluated. MMP-7 protein expression and its polymorphisms were investigated in a total of 400 patients using immunohistochemistry and TaqMan SNP genotyping assays. The correlation of MMP-7 expression with clinicopathological characteristics, including tumor location, tumor size, histologic type, lymphatic invasion, vascular invasion, pathological T stage, pathological TNM stage, residual tumor, and CEA level, was investigated. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using a multivariate Cox proportional hazards regression model. MMP-7 expression was found in 283 of 400 (70.75%) gastric cancer tissues. Expression of MMP-7 was significantly associated with poor clinicopathological characteristics, including vascular invasion (OR = 6.61, 95 % CI = 4.26 – 9.89, p = 0.024 ), lymphatic invasion (OR = 8.17, 95 % CI = 4.47 – 12.39, p = 0.017 ), undifferentiated histologic type (OR = 2.46 ; 95% CI, 1.31–4.52; p = 0.014 ), higher TNM stage (stage IV) (OR = 1.48, 95 % CI = 1.08 – 3.08, p = 0.047 ), and high CEA level (OR = 5.96, 95 % CI = 2.12 – 8.12, p = 0.026 ). We further observed a significant association of the variant genotype; gastric cancer patients carrying GG of MMP-7 (-181A/G; rs11568818) had a greater increased risk of MMP-7 expression than did wild-type (WT) carriers (AG: odds ratio OR = 5.67 ; 95 % CI = 1.57 – 7.23 ; p = 0.024 and GG: OR = 8.32 ; 95 % CI = 2.94 – 11.42 ; p = 0.016 ). These findings suggest that MMP-7 expression can be used to predict the prognosis of gastric cancer patients.